SDA LEADERSHIP STYLE IN INDONESIA - Mantiri, Oktavian (11th International Scholars Conference, 2016)
This paper is a qualitative study that seeks to shed light on the leadership style of Adventist leaders in Indonesia. Arguably, much of the literature in the field of Adventist education and leadership come from western hemisphere. Little can be found on the area of Asian leadership style. The driving force to do this research is the fact that Adventist institution is a world institution which may have some bearings on the Adventist leadership style in the east. This paper explores the perception of Indonesian SDA members about the church leadership style in Indonesia. An online survey was posted on the internet and generated 330 people participants. However, due to its nature being an open survey, the completion rate is somewhat low. The data revealed that in general SDA leaders in Indonesia are quality leaders. Despite the fact however, more than 90 percent indicated the need of continuous leadership training. The author of this paper however acknowledges the limitations of this study such as low completion rate and difficulty to generate participants. On the other hand however, the result arguably reflected the current perceptions of SDA leadership style in Indonesia and that further research in this area needs to be followed up.